National intellectual capital: Comparison of the Nordic Countries - 林月雲; Leif Edvinsson (Journal of Intellectual Capital, 2008)
Purpose – This study proposes a model to measure national intellectual capital that can be easily replicated for trend analysis. Key dimensions include human capital, market capital, process capital, renewal capital, and financial capital. Design/methodology/approach – With longitudinal data spanning the period from 1994 to 2005, this study compares the national intellectual capital of 40 countries based on an IC map of 29 indicators. Findings – The overall intellectual capital ranking of the five Nordic countries is: 1 Sweden, 2 Finland, (3 Switzerland), 4 Denmark, (5 USA), 6 Norway, and 7 Iceland in the 40-country list. Practical implications – The results confirm the general perception that the Nordic countries have a high degree of national intellectual capital. The research findings clarify the status of national intellectual capital of the Nordic countries, thereby providing valuable information for stakeholders and policy makers to formulate effective strategies for building sustainable national competitiveness. In order to do this, it is necessary to elaborate on the proposed IC framework and to gather relevant and valid IC indicators. Originality/value – The results of this study can provide a map for the Nordic countries – and other countries – as they prepare for future challenges, such as those associated with globalization and its implications on potential wealth creation. A deeper study of why and how might be a part of forthcoming studies.